Answer:
2n+7
Step-by-step explanation:
Answer:
c = 36.06
Step-by-step explanation:
a² + b² = c²
20² + 30² = c²
400 + 900 = c²
c² = 1300
![\sqrt{c^2} =\sqrt{1300}](https://tex.z-dn.net/?f=%5Csqrt%7Bc%5E2%7D%20%3D%5Csqrt%7B1300%7D)
c = 36.06
Answer:
Step-by-step explanation:
17.3664
Answer:
The roots of equations are as m =
And n =
Step-by-step explanation:
The given quadratic equation is 2 x² + 6 x - 1 = 0
This equation is in form of a x² + b x + c = 0
Let the roots of the equation are ( m , n )
Now , sum of roots = ![\frac{ - b}{a}](https://tex.z-dn.net/?f=%5Cfrac%7B%20-%20b%7D%7Ba%7D)
And products of roots = ![\frac{c}{a}](https://tex.z-dn.net/?f=%5Cfrac%7Bc%7D%7Ba%7D)
So, m + n =
= - 3
And m × n = ![\frac{ - 1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B%20-%201%7D%7B2%7D)
Or, (m - n)² = (m + n)² - 4mn
Or, (m - n)² = (-3)² - 4 (
)
Or, (m - n)² = 9 + 2 = 11
I.e m - n = ![\sqrt{11}](https://tex.z-dn.net/?f=%5Csqrt%7B11%7D)
Again m + n = - 3 And m - n = ![\sqrt{11}](https://tex.z-dn.net/?f=%5Csqrt%7B11%7D)
Solving this two equation
(m + n) + ( m - n) = - 3 + ![\sqrt{11}](https://tex.z-dn.net/?f=%5Csqrt%7B11%7D)
I.e 2 m = - 3 + ![\sqrt{11}](https://tex.z-dn.net/?f=%5Csqrt%7B11%7D)
Or, m = ![\frac{-3}{2} + \frac{\sqrt{11} }{2}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%7D%7B2%7D%20%2B%20%5Cfrac%7B%5Csqrt%7B11%7D%20%7D%7B2%7D)
Similarly n =
Hence the roots of equations are as m =
And n =
Answer